The Effect of Providing Compensation on Employees' Work Productivity At Pt Berkah Dwiko Jaya in Baubau City - Rahmad Hasmin. H; Hastuti Hastuti; Husnah Katjina (AIQU: Journal Multidiscipliner of Science, 2023)
This research aims to determine the effect of providing compensation on the work productivity of PT employees. Blessings of Dwiko Jaya in Baubau city. The research method used is descriptive with simple linear analysis. This research was conducted at PT. Berkah Dwiko Jaya Baubau City, Kokalukuna District, Kadolomoko Village, Baubau City. The results of the analysis show that providing compensation has a positive effect on employee work productivity. These results indicate that providing appropriate compensation that is accepted by employees will increase employee work productivity at PT. Blessings Dwiko Jaya Baubau City. Providing compensation also contains a professional relationship where one of the main goals of employees' work is to get compensation to meet various needs, while on the PT or company side they pay employees so that employees can carry out their work in accordance with the company's wishes and expectations with the main goal being to be able to advance the course of the company's business. By providing compensation that is more appropriate and accepted by employees because it is in accordance with the energy and abilities expended and respecting employees' hard work, employees will behave more professionally by working seriously and making various efforts to achieve better work results so that productivity work could increase further.